Poikilitic textures, heteradcumulates and zoned orthopyroxenes in the Ntaka Ultramafic Complex, Tanzania: Implications for crystallization mechanisms of oikocrysts - Barnes, S.; Mole, D.; Le Vaillant, M.; Campbell, M.; Verrall, M.; Roberts, M.; Evans, Noreen (Oxford University Press, 2016)
The late Proterozoic Ntaka Ultramafic Complex is a body of dominantly pyroxenitic cumulate rocks containing cyclic alternations of olivine-orthopyroxene cumulates. Chemical zoning in the pyroxenes has been imaged at 25-40 µm resolution using desktop microbeam X-ray fluorescence mapping followed up with laser ablation-inductively coupled plasma mass spectrometry analysis for minor and trace elements on selected samples. Poikilitic and granular harzburgites are finely intermingled, in some cases on a centimetre scale in the same thin section. Poikilitic varieties display spectacular textures, ranging from isolated equant orthopyroxene oikocrysts within olivine-rich heteradcumulate harzburgites to rocks composed entirely of interlocking centimetre-sized anhedral orthopyroxene oikocrysts containing sharply bounded idiomorphic Cr-enriched cores. The poikilitic harzburgites are interlayered with cumulate pyroxenites in which orthopyroxene grains show a variety of zoning patterns: Cr-rich cores similar to those in the oikocrysts; sharply bounded oscillatory zoned cores; and reverse zoning with Cr-poor cores and Cr-enriched rims. A further variation is the presence of a mingled harzburgite lithology in which dunite or poikilitic harzburgite is invaded on a centimetre scale by diffuse vein networks or patches of coarse orthopyroxenite. This range of textures and lithologies attests to a more complex set of processes than implied by the standard cumulus theory model in which oikocrysts are considered to have crystallized from intercumulus liquid within a permeable crystal mush. A range of hypotheses is proposed, including infiltration metasomatism of original olivine cumulates by migrating orthopyroxene-saturated pore fluid; however, the textural relationships, whole-rock chemistry and Cr zoning within the grains can best be explained by a model in which the orthopyroxene oikocrysts form in part or whole as mechanically accumulated cumulus grains. The complexity of zoning patterns is attributed to stirring of entrained olivine and orthopyroxene crystals within a heterogeneous flowing crystal mush, where the transporting magma has a wide range of silica contents owing to poorly stirred incorporation of siliceous country-rock material. The Cr-rich orthopyroxenite component grew from Sienriched chromite-saturated magma. Mingled lithologies developed after accumulation as a result of percolation and infiltration metasomatism by Si-enriched liquid derived by melting of xenoliths within the crystal pile. The model may be more generally applicable: dunite-harzburgite cycles, common in many layered intrusions, may reflect variable degrees of contamination rather than cycles of fractional crystallization and replenishment.